Inverted Linear Correlation Between the Catalytic Activity of Iron Phthalocyanines and the Formal Potential of the Catalyst in the Electrooxidation of L-Cysteine - Zagal-Moya, J; Zagal-Moya, J; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Silva-Rojas, J; Silva-Rojas, J (2012)
Sin Editorial Disponible